Rearing business analysis of Brahman Cross Breed ex import cattle with a partnership between corporations and smallholder farms - Restu Mekar Muninggar; Rini Widiati; Tri Satya Mastuti Widi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2021)
The objective of the research was to study the partnership rearing scheme of Brahman Cross (BX) cattle ex import between corporations and smallholder farmers to determine the financial and economic feasibility of the business and the factors that affected the production of rearing cattle. The research was conducted in farmers groups in West Java, Central Java, and Yogyakarta, which developed a partnership with feedlot importer, PT.X. Twenty-eight farmer respondents were determined by purposive sampling. Each of them kept ten male and female calves of BX. Collecting data was done by survey method through interviews using a questionnaire. The investment feasibility criteria were NPV, IRR, B/C ratio and payback period, followed by a sensitivity analysis. Analysis of the factors that affect the production of rearing cattle using multiple linear regression. The results showed that the parties involved in the partnership, PT X, were banks that fund all financing, insurance services, and farmers. The average initial weight, final weight, maintenance time, and ADG were 145.75 ± 34.54 kg, 318.50 ± 52.27 kg, 9.65 ± 1.7 months, 0.61 ± 0.17 kilograms. The results of the analysis of the feasibility with an investment period of 5 years and an interest rate of 9%, micro-credit 13.5%, and commercial 18% are financially and economically feasible to run. Provision of concentrate and initial body weight significantly (P <0.5) had a positive effect on the production (ADG) of rearing cattle. The partnership scheme developed by PT X can be beneficial to all parties involved.